First record of Triassic Rhynchosauria (Reptilia: Diapsida) from the Lower Zambezi Valley, Zimbabwe - Raath, Michael A; Oesterlen, P M; Kitching, James W (Bernard Price Institute for Palaeontological Research, 1992)
True rhynchosaurids are described from Zimbabwe for the first time. The fossils occur as partially associated skeletons and scattered isolates in upward-fining, micaceous fluvial sandstones of the Pebbly Arkose Formation (late Triassic) in the Western Cabora Bassa Basin, Lower Zambezi Valley. On the grounds that the dentary of the Zimbabwean form possesses a row of small, conical lingual teeth in addition to a palisade row of penicillate teeth on the occlusal surface, it is concluded that the taxon present is Hyperodapedon sp., and that it is closely related to a rhynchosaurid described from Tanzania. One bone identified as a prosauropod dinosaurian femur was found associated with the Zimbabwean rhynchosaurids. The late Triassic age suggested by the presence of advanced rhynchosaurids is supported by the occurrence of the typical Triassic fossil plant genus Dicroidium, and by the general stratigraphy of the beds which contain the fossils (i.e. the fossil-bearing beds are underlain by beds of mid-Triassic age or younger, and are overlain by beds of latest Triassic or early Jurassic age)
Keywords: Stormberg; Rhodesia; molteno